Intentional Living : Choosing a Life that Matters - Maxwell, John C., 1947- (New York Center Street, 2015)
AJohn C. Maxwell, #1 New York Times bestselling author, helps readers take the first steps to living a life that matters in INTENTIONAL LIVING. We all have a longing to be significant. We want to make a contribution, to be a part of something noble and purposeful. But many people wrongly believe significance is unattainable. They worry that it's too big for them to achieve. That they have to have an amazing idea, be a certain age, have a lot of money, or be powerful or famous to make a real difference. The good news is that none of those things is necessary for you to achieve significance and create a lasting legacy. The only thing you need to achieve significance is to be intentional. And to do that, all you need to do is start. You can't make an impact sitting still and doing nothing. Every major accomplishment that's ever been achieved started with a first step. Sometimes it's hard; other times it's easy, but no matter what, you have to do it if you want to get anywhere in life. In INTENTIONAL LIVING, John Maxwell will help you take that first step, and the ones that follow, on your personal path through a life that matters
Include Notes
Keywords: Conduct of life -- Self-actualization (Psychology) -- Self-realization